Hollow viscus perforation with gas under diaphragm: a misnomer? - Dutta, Pooja; Wadhawan, Gaurav; Arora, Raghav; Sharma, Shruti (International Journal of Research in Medical Sciences, 2023)
Background: Hollow viscus perforation is suspected when radiographs show the presence of gas under diaphragm and is usually an indication for surgical abdominal exploration. This is significant because in cases of hollow viscous perforation, plain radiography may be used as the first line of diagnosis. Concerns regarding diagnosing those 30% cases of hollow viscus perforation which was not detected by the plain radiography. Methods: A bound prospective study of patients who were managed for perforated hollow abdominal viscus, when no abnormality was appreciated on radiographs, confirmation was done either on the basis of clinical examination, further investigations or by exploratory laparotomy performed on basis of selection of cases. Results: Based on the study, 15 patients were found with no gas under diaphragm on radiographs and perforation was confirmed on the grounds of clinical, physical examination, further investigations or by exploratory laparotomy on basis of cases. The results obtained in the present study shows male predominance, duodenal perforation being the most common perforation amongst hollow viscus perforations and age group of 20-40 years were affected mainly. Conclusions: It is important to note that not all the cases of pneumoperitoneum indicate perforated abdominal viscus or vice versa. This study highlights the difficulty in pre-operative diagnosing pneumoperitoneum with upright chest and abdominal X-rays provided its sensitivity varied from 50-98%.